BNDES credit, dependence on external finance, and R&D intensity in the Brazilian industrial sectors (1998-2014) - Souza, Eduardo Correia de; Ribeiro, Priscila Fernandes; Mattos, Eduardo Souza (Estudos Econômicos (São Paulo), 2020)
This paper aims to test if the BNDES plays a role compensating for potential credit market imperfections, in what concerns R&D investments. In order to do that, we employ a regression with interaction analysis inspired by Maskus et al. (2012). We use data on 22 Brazilian industrial sectors, having as sources the PINTEC, the BNDES and the PIA, covering 6 triennia from 1998 to 2014. Our results offer some support to the hypothesis of a positive BNDES role: the BNDES credit is more positively correlated with the R&D intensity in sectors/periods in which dependence on external financial capital is bigger.